Optimization of Plant Growth Regulators for Efficient Embryogenic Callus Induction and Subsequent Plant Regeneration in Two Indigenous Aromatic Rice Varieties of Bangladesh (Plant Tissue Culture and Biotechnology, 2025)
An efficient regeneration protocol via somatic embryogenesis for two aromatic Indica rice varieties, Kalijira and Tulshimala was developed. Using mature, dehusked seeds, the process involved callus initiation, embryo development and plant regeneration involving MS medium accompanied with specific concentrations of the auxins 2,4-D and NAA, along with the cytokinin BAP. Callus induction was optimized at 2 mg/l 2,4-D, and 1 mg/l NAA, yielding initiation rates of 87% for Kalijira and 95% for Tulshimala. The medium supplemented with 2 mg/l 2,4-D supported robust embryogenic calli development. Mature embryos were successfully regenerated on media comprising 0.1 mg/l NAA and 2.5 mg/l BAP for Kalijira while 2 mg/l BAP for Tulshimala, with 35% of Kalijira calli forming multiple shoots and 65% rooting, on the other hand Tulshimala achieved 70% shoot formation and 100% rooting. Transplanted plantlets adapted well, showing high survival rates.Plant Tissue Cult. & Biotech. 34(2): 153-164, 2024 (December)